The neurotoxicity of amyloid β-protein oligomers is reversible in a primary neuron model. Issue 1 (December 2017) - Tanokashira, Daisuke; Mamada, Naomi; Yamamoto, Fumiko; Taniguchi, Kaori; Tamaoka, Akira; Lakshmana, Madepalli; Araki, Wataru
Abstract Alzheimer's disease (AD) is characterized by the accumulation of extracellular amyloid β-protein (Aβ) and intracellular hyperphosphorylated tau proteins. Recent evidence suggests that soluble Aβ oligomers elicit neurotoxicity and synaptotoxicity, including tau abnormalities, and play an initiating role in the development of AD pathology. In this study, we focused on the unclarified issue of whether the neurotoxicity of Aβ oligomers is a reversible process. Using a primary neuron culture model, we examined whether the neurotoxic effects induced by 2-day treatment with Aβ42 oligomers (Aβ-O) are reversible during a subsequent 2-day withdrawal period. Aβ-O treatment resulted in activation of caspase-3 and eIF2α, effects that were considerably attenuated following Aβ-O removal. Immunocytochemical analyses revealed that Aβ-O induced aberrant phosphorylation and caspase-mediated cleavage of tau, both of which were mostly reversed by Aβ-O removal. Furthermore, Aβ-O caused intraneuronal dislocation of β-catenin protein and a reduction in its levels, and these alterations were partially reversed upon Aβ-O withdrawal. The dislocation of β-catenin appeared to reflect synaptic disorganization. These findings indicate that removal of extracellular Aβ-O can fully or partially reverse Aβ-O-induced neurotoxic alterations in our neuron model. Accordingly, we propose that the induction of neurotoxicity by Aβ oligomers is a reversible process, which has important implications for the development of AD therapies.